The Path to Urbanism. Exploring the Anatomy and Development of Early Urbanism in Northern Mesopotamia. Five Years of Investigations by the Danish Archaeological Expedition to Iraq - Skuldbøl, Tim Boaz Bruun; Colantoni, Carlo (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
Urbanism is a key milestone in history and understanding the nature of the urbanisation process, and its diversity, is one of archaeology’s primary challenges (see Kintigh et al. 2014: 10). One of the keys to understanding this process in Mesopotamia are the radical transformations in organisational practices and use of space that early societies underwent along their path to urbanism.